Impact factors analysis: Differences in high-level golfers - Brozka, M.; Kotrba, M.; Zahalka, F.; Gryc, T. (International Journal of Performance Analysis in Sport, 2023)
The best golfers exceed the length and accuracy of their driver strokes. The distance and accuracy of the strokes are determined by the impact factors between the club and the ball. However, it is not known whether there are differences in the level and consistency of impact factors within high-level performance players. This study aims to determine the level and variability of impact factors during full swing and evaluate the differences between high-level golfers. Professional and elite players achieved significantly higher clubhead speed as opposed to skilled players, which subsequently caused higher smash factor and ball speed. They also produced significantly lower launch angle with eight iron and lower spin rate with driver. Unexpectedly, the difference in consistency was found only between professional and skilled golfers in the variation of the smash factor which led to a lack of consistency in ball speed. In general, the results indicate that all performance groups are able to consistently repeat the impact factors during the full swing; however, the level of the impact factors distinguishes professionals and elites from skilled golfers. This study therefore suggests that the focus should be primarily on the quality of the golf swing and subsequently on its repeatability.